2018
DOI: 10.3389/fpsyg.2018.01818
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Socioeconomic Status as a Modulator of the Bilingual Advantage in Cognitive Ability

Abstract: Between-group variability in socioeconomic status (SES) has been identified as a potentially important contributory factor in studies reporting cognitive advantages in bilinguals over monolinguals (the so called “bilingual advantage”). The present study addresses the potential importance of this alternative explanatory variable in a study of low and high SES bilingual and monolingual performance on the Simon task and the Tower of London (TOL) task. Results indicated an overall bilingual response time advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 48 publications
(50 reference statements)
4
55
4
Order By: Relevance
“…Moreover, the current study found that some demographic factors were significantly associated with cognitive control in some dimensions. Specifically, age and education were associated with mental set shifting, whereas SES associated with inhibition, which conflicts with some recent studies in that SES is related to conflict monitoring (reflected by response times) (e.g., Naeem et al, 2018;Xie and Pisano, 2019). Nevertheless, these results are generally in line with the findings that higher education and SES are correlated positively with cognitive control, whereas age is positively correlated with cognitive control for children and young adult participants but negatively correlated with cognitive control for older adults (Valian, 2015;van den Noort et al, 2019;Xie and Pisano, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the current study found that some demographic factors were significantly associated with cognitive control in some dimensions. Specifically, age and education were associated with mental set shifting, whereas SES associated with inhibition, which conflicts with some recent studies in that SES is related to conflict monitoring (reflected by response times) (e.g., Naeem et al, 2018;Xie and Pisano, 2019). Nevertheless, these results are generally in line with the findings that higher education and SES are correlated positively with cognitive control, whereas age is positively correlated with cognitive control for children and young adult participants but negatively correlated with cognitive control for older adults (Valian, 2015;van den Noort et al, 2019;Xie and Pisano, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…The studies conducted in the context of Head Start programs or in schools that support low income and at‐risk students document learners’ positive development trajectories during the transition from preschool to kindergarten, particularly when the L1 is spoken in the home; they thus underscore the importance of early start for all learners. In this area, see also studies by Engel de Abreu, Cruz‐Santos, Tourinho, Martin, and Bialystok (); Naeem, Filippi, Periche‐Tomas, Papageorgiou, and Bright (); and Nair, Biedermann, and Nickels () where socioeconomic status is an important factor in the investigation. Might these results point to the possibility that early language study and bilingualism represent, at least in part, a solution for the achievement gap?…”
Section: Discussionmentioning
confidence: 98%
“…In the last decade, there has also been growing controversy around the claims of the bilingual advantage with an increasing number of studies showing null results (e.g., Duñabeitia, Hernandez, Anton, et al, 2014;Paap & Greenberg, 2013;Paap, Johnson & Sawi, 2014). Factors such as immigration status (Kousaie & Phillips, 2012), language history, socioeconomic status (Naeem, Filippi, Periche-Tomas, Papageorgiou & Bright, 2018;Morton & Harper, 2007), intelligence and culture (Yang, Yang, & Lust, 2011) which were not always included in earlier studies have been cited as having potentially confounding effects (Lehtonen et al, 2018). In their meta-analysis of results from non-verbal interference tasks, Hilchey and Klein (2011) found that bilingual advantages in executive control tend to occur in studies with small samples while null results were more likely with larger samples.…”
Section: Challenges To the Bilingual Advantage Hypothesismentioning
confidence: 99%